Molecular developmental analysis of artificial selection response in the male sex combs of Drosophila melanogaster - Cheng, Sheng (My University, 2014)
Evolutionary innovations, at the molecular level, represent the novel establishment of regulation networks among previously unconnected genes. Understanding the cellular and molecular mechanisms that underlies the development of such innovations is of central importance in evolutionary-developmental research (evo-devo). The sex comb of Drosophila is an excellent model to study the molecular basis of evolutionary innovations. Highline and Lowline are two artificial selected D. melanogaster lines differing in the number of sex comb bristles. It was expected that the “cross-regulation loop” between two transcription factors, Doublesex male isoform (DSXM) and Sexcombs reduced (SCR), evolves rapidly and promotes the morphological evolution of sex combs. We used immunofluorescent technique (antibody staining) to compare the expression of DSXM and SCR in the forelegs of three different lines (Highline, Wildtype and Lowline). We hypothesized that artificial selection will increase expression of DSXM and SCR in the Highline and reduce expression in the Lowline. The fluorescent pictures of antibody staining experiments indicate that the expression region of DSXM in the Highline is significantly higher than the expression region in the Lowline, and the expression levels of SCR has minor difference among the three lines. DSXM expression is altered by the artificial selection, but SCR expression is not. The influence of artificial selection appears to have been constrained by development. Our investigation provides an approach to test the validity of the models of cross-regulation s between SCR and DSXM during development.
Keywords: Melanogaster; Sex Combs; artificially selected lines; doublesex; Sexcomb reduced; Developmental Biology; Developmental Biology